2012
DOI: 10.1134/s1061933x12020111
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-induced redox transformations in Langmuir monolayers of double-decker cerium bis[tetra-(15-crown-5)-phthalocyaninate] and multistability of its Langmuir-Blodgett films

Abstract: The spectral, electrochemical, and optical properties of Langmuir-Blodgett films (LBFs) and cast films from a solution of new double decker cerium bis[tetra (15 crown 5) phthalocyaninate] (Ce(R 4 Pc) 2 ) are studied. Based on analysis of compression isotherms and quantum chemical calculations, schemes of the organization of Ce(R 4 Pc) 2 molecules at different states of its monolayers are proposed. Cor relation dependences are determined in order to relate the optical and electrochemical characteristics of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…It was found that no analogous spectral changes occur upon spreading and compression of monolayers of these complexes, that is in conformity with the fact that these lanthanide ions can only exhibit a 3+ oxidation state in these complexes. 26,38 Spectra of monolayer of unsubstituted CePc 2 , in which Ce 4+ state is much more stable than in crown substituted complex, 7,15,34 also do not undergo such alterations upon deposition and compression and do not possess the band at about 500 nm ( Figure 6, curve 1). At last, the positions of bands at about 500 nm in DRAS of trivalent lanthanide complexes at the air−water interface recorded at 5 mN m −1 surface pressure ( Figure 6, curves 2− 6) are linearly correlated with corresponding ionic radii ( Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that no analogous spectral changes occur upon spreading and compression of monolayers of these complexes, that is in conformity with the fact that these lanthanide ions can only exhibit a 3+ oxidation state in these complexes. 26,38 Spectra of monolayer of unsubstituted CePc 2 , in which Ce 4+ state is much more stable than in crown substituted complex, 7,15,34 also do not undergo such alterations upon deposition and compression and do not possess the band at about 500 nm ( Figure 6, curve 1). At last, the positions of bands at about 500 nm in DRAS of trivalent lanthanide complexes at the air−water interface recorded at 5 mN m −1 surface pressure ( Figure 6, curves 2− 6) are linearly correlated with corresponding ionic radii ( Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…As it is known, [17][18][19][21][22][23][24][25][26] cerium atom in sandwich-type phthalocyaninates can exhibit two oxidation states: +3, as all the lanthanides and +4. Special stability of the configuration of the 4f 0 free shell makes tetravalent state of the cerium ion quite stable.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18] In this light, phthalocyaninates of lanthanides with variable valence attract great interest due to possibility of realization of additional redox-process associated with change of metal center oxidation state. [18][19][20][21][22][23][24][25] On the other hand, practical application of such compounds requires knowledge on the influence of external factors on properties of redox-processes taking place in these systems. One of such factors is the presence of oxidizers, and, primarily, atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…they take an «edge-on» orientation as a consequence of the stabilizing π-π stacking interactions. Evidently, low monolayer area values are recorded in such situations, which correspond precisely to such an orientation of the aromatic molecules [31][32][33][34][35]. In contrast, "face-on" orientation of anthraquinone moiety is preserved even at a high surface density of monolayer.…”
Section: Monolayers Of Amphiphilic Ligands Lc12 Lc18 and L*c12 On A mentioning
confidence: 88%